Modification of plant Rac/Rop GTPase signalling using bacterial toxin transgenes. (8th November 2012) - Singh, Manoj K.; Ren, Fugang; Giesemann, Torsten; Bosco, Cristina Dal; Pasternak, Taras P.; Blein, Thomas; Ruperti, Benedetto; Schmidt, Gudula; Aktories, Klaus; Molendijk, Arthur J.; Palme, Klaus
Summary: Bacterial protein toxins which modify Rho GTPase are useful for the analysis of Rho signalling in animal cells, but these toxins cannot be taken up by plant cells. We demonstrate in vitro deamidation of Arabidopsis Rop4 by Escherichia coli Cytotoxic Necrotizing Factor 1 (CNF1) and glucosylation by Clostridium difficile toxin B. Expression of the catalytic domain of CNF1 caused modification and activation of co‐expressed Arabidopsis Rop4 GTPase in tobacco leaves, resulting in hypersensitive‐like cell death. By contrast, the catalytic domain of toxin B modified and inactivated co‐expressed constitutively active Rop4, blocking the hypersensitive response caused by over‐expression of active Rops. In transgenic Arabidopsis, both CNF1 and toxin B inhibited Rop‐dependent polar morphogenesis of leaf epidermal cells. Toxin B expression also inhibited Rop‐dependent morphogenesis of root hairs and trichome branching, and resulted in root meristem enlargement and dwarf growth. Our results show that CNF1 and toxin B transgenes are effective tools in Rop GTPase signalling studies.